2018
DOI: 10.3389/fmicb.2018.02691
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Microbiota of Dairy Cows With Clinical and Subclinical Endometritis

Abstract: The objective of this study was to characterize the uterine microbiota of dairy cows with clinical and subclinical endometritis and to identify the potential bacterial genera as well as their interactions associated with uterine disease. Uterine flush samples (n = 27) were collected from 13 healthy, 5 subclinical endometritic (SE), and 9 clinical endometritic (CE) cows at 30 days postpartum. Microbial DNA from uterine flush samples was subjected to sequencing of the 16S rRNA gene on the Illumina MiSeq platform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
68
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 53 publications
7
68
2
3
Order By: Relevance
“…Santos et al [5] and Wang et al [21] reported that Proteobacteria was the most abundant phylum in the uterine microbiota of healthy cows; however, in this study, Proteobacteria was the second and third most abundant phylum in the samples obtained during summer and winter, respectively. The predominant taxa of Proteobacteria in the healthy uterine microbiota are also unclear; Santos et al [5] have indicated Pasteurella spp., and Bicalho et al [22] have demonstrated Escherichia spp.…”
Section: Discussioncontrasting
confidence: 73%
See 4 more Smart Citations
“…Santos et al [5] and Wang et al [21] reported that Proteobacteria was the most abundant phylum in the uterine microbiota of healthy cows; however, in this study, Proteobacteria was the second and third most abundant phylum in the samples obtained during summer and winter, respectively. The predominant taxa of Proteobacteria in the healthy uterine microbiota are also unclear; Santos et al [5] have indicated Pasteurella spp., and Bicalho et al [22] have demonstrated Escherichia spp.…”
Section: Discussioncontrasting
confidence: 73%
“…Santos et al [5] and Wang et al [21] reported that Proteobacteria was the most abundant phylum in the uterine microbiota of healthy cows; however, in this study, Proteobacteria was the second and…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations